Aggregate Effects from Public Works: Evidence from India - Cook, C. Justin; Shah, Manisha (The Review of Economics and Statistics, 2022)
This paper explores the aggregate economic effects from India's National Rural Employment Guarantee Scheme (NREGS), which provides up to 100 days of labor to rural laborers at the mandated minimum wage. We examine the within-district change to nighttime lights, a proxy for economic development, and banking deposits using the staggered program rollout for identification. We find consistent and robust evidence that NREGS increased aggregate economic output by 1% to 2% per capita measured by nighttime lights. This effect, however, is not equal across districts. We observe no positive effect of the program in poorer districts, illuminating an important source of heterogeneity.